Extraction and characterisation of apatite- and tricalcium phosphate-based materials from cod fish bones - Piccirillo, C. (2013)
Apatite- and tricalcium phosphate-based materials were produced from codfish bones, thus converting a waste by-product from the food industry into high added-valued compounds. The bones were annealed at temperatures between 900 and 1200 degrees C, giving a biphasic material of hydroxyapatite and tricalcium phosphate (Ca-10(PO4)(6)(OH)(2) and beta-Ca(PO4)(3)) with a molar proportion of 75:25, a material widely used in biomedical implants. The treatment of the bones in solution prior to their annealing changed the composition of the material. Single phase hydroxyapatite. chlorapatite (Ca-10(PO4)(6)Cl-2) and fluorapatite (Ca-10(PO4)(6)F-2) were obtained using CaCl2 and NaF solutions, respectively. The samples were analysed by several techniques (X-ray diffraction, infrared spectroscopy, scanning electron microscopy and differential thermal/thermogravimetric analysis) and by elemental analyses, to have a more complete understanding of the conversion process. Such compositional modifications have never been performed before for these materials of natural origin to tailor the relative concentrations of elements. This paper shows the great potential for the conversion of this by-product into highly valuable compounds for biomedical applications, using a simple and effective valorisation process.